Macroeconomic Factors that Conditioned International Migration from Ecuador: A Scientific Approach for the Period 2000-2021 - Bautista, María Gabriela González; Moreno, Sthefanny Jhoanna Chamorro; Moreano, Eduardo Germán Zurita; Martínez, Magda Francisca Cejas (Migration Letters, 2023)
Migration since ancient times has been a global phenomenon that is determined by many factors that influence people’s decision to look for another country to settle. The research from a macroeconomic perspective analyzes in depth the factors that explain migration in the case of Ecuador, seeking to establish whether the changes suffered by the country have had an impact on the decisions to migrate. A Vector Autoregressive (VAR) model was chosen seeking to characterize the simultaneous interactions between the group of variables and establish whether the relationships are transmitted in the long term. The results indicate that the macroeconomic variable that exerts the greatest influence is unemployment, since an increase in the unemployment rate translates into an increase of 0.74% in migration to countries that offer job stability.